Coastal Mass Tourism 2004
DOI: 10.21832/9781873150702-015
|View full text |Cite
|
Sign up to set email alerts
|

13. Sustainable Tourism: Utopia or Necessity? The Role of New Forms of Tourism in the Aegean Islands

Abstract: Tourism is a major activity in the Greek islands. Its development during recent decades has stopped the economic and demographic decline of the area. The paper develops a framework for the appraisal of tourism's sustainability in the Greek islands, and it is concluded that the conventional tourist model, based on sun, sea and sand (3S) has failed to promote sustainability due to the limited economic benefits for host communities and growing environmental pressures. The latest trend in Greece and elsewhere is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 4 publications
0
28
0
6
Order By: Relevance
“…Tourism pressure indicators for Kos are higher than for Rhodes, one of the most favoured tourist destinations worldwide: the total number of beds km -2 in Kos increased from 14.7 in 1981to 120.18 in 1997and 163.2 in 2012(Spilanis & Vayanni, 2004. The 4,262 bedrooms (52 hotels) registered in 1980 became 13,314 (151 hotels) in 1990 and climbed to approximately 50,000 in 2010 (300 hotels).…”
Section: Human Pressuresmentioning
confidence: 97%
“…Tourism pressure indicators for Kos are higher than for Rhodes, one of the most favoured tourist destinations worldwide: the total number of beds km -2 in Kos increased from 14.7 in 1981to 120.18 in 1997and 163.2 in 2012(Spilanis & Vayanni, 2004. The 4,262 bedrooms (52 hotels) registered in 1980 became 13,314 (151 hotels) in 1990 and climbed to approximately 50,000 in 2010 (300 hotels).…”
Section: Human Pressuresmentioning
confidence: 97%
“…In contrast, despite being part of the tourism package, many islets surrounding islands are inadequately researched. For instance, many tourism studies undertaken in the Aegean and Mediterranean islands (e.g., Andriotis, 2008;Sharpley, 2001;Spilanis & Vayanni, 2003;Sterren, 2007) focus on main islands like Crete, Santorini, Majorca, Malta, Canary, Rhodes, and Paros while islets such as Nea Kameni, Palaia Kameni, Archi, Chalki, Dragonada, and Elassa in the Aegean alone are not investigated. It is thus observed that whenever an islet is under the sovereignty of another land, research conducted on the islet is usually undertaken in conjunction with the mainland.…”
Section: Gap In the Literaturementioning
confidence: 99%
“…Samothraki is a mountainous island of the NE Aegean, Greece (Figure 1), with an area of 178 km 2 and 2,859 permanent residents that are mostly occupied with agriculture (mainly livestock keeping) and seasonal tourism services. Samothraki attracts about 40,000 visitors per year, in a relatively short season (Fischer-Kowalski et al, 2011); with 0.5 tourist beds per inhabitant, it ranks in the lower range of Greek islands (Spilanis & Vayanni, 2004). It has numerous freshwater streams and outstanding natural beauty (Natura 2000, for the most part), as well as significant cultural heritage, and is at the crossroads of development pathways.…”
Section: Towards Sustainability Transformation Of An Islandmentioning
confidence: 99%